Environmental injustices in immigrant detention: How absences are embedded in the National Environmental Policy Act process. (June 2021) - Edwards, Michelle L.; Luna, Briana; Edwards, Hannah
The United States' National Environmental Policy Act is a knowledge production process required by federal government agencies to assist in their evaluation of the environmental (and social) impacts of proposed federal agency actions prior to their implementation. The U.S. Department of Homeland Security, which manages immigrant detention in the United States, is included among these federal agencies. Using Texas as a case study, we explore how the National Environmental Policy Act process, as it relates to immigrant detention, systematically produces ignorance while also producing knowledge. We identify four forms of absence: absence of process in Department of Homeland Security's use of Categorical Exclusions and programmatic Environmental Assessments, absence of actors in the exclusion of people who are detained as an "affected" social group, absence of alternatives in how "meaningful alternatives" are identified in Environmental Assessments, and absence of discourse with the public in the Environmental Assessment process. In addition, we consider how these absences reflect and perpetuate existing social and environmental inequalities.